Defining rape culture : gender, race and the move toward international social change - Hayes, Rebecca M. (Emerald studies in criminology, feminism and social change., 2023)
Rape culture, a colloquial term often used to describe society's normalization and cultural acceptance of sexual violence, especially of men towards women, can be defined in a variety of ways. Academic discussions surrounding this topic often lack the theorization needed to elevate these conversations from their specific contexts to a broader, more conscious cultural awareness. Providing clearly defined, historical and cross-cultural definitions of this well-used term, Defining Rape Culture addresses current debates with a fresh international perspective that does not limit itself to whiteness or the Global North. Examining the culture around sexual violence through an intersectional feminist lens, Rebecca M. Hayes interrogates the historical origins of sexual violence that are steeped in colonization and white supremacy, proving how the thread of rape culture has persisted even among very different cultures. Tackling how legal and institutional indifference to sexual misconduct has allowed it to fester unpunished, chapters also reveal the role that social media has played in exposing the shared trauma that rape culture perpetuates. From #notallmen to #MeToo, Defining Rape Culture acts as an in-depth primer on how these outdated attitudes continue to persist, but also the role we can play in shifting this cultural mindset and create lasting social change.